Cover Image, Volume 176A, Number 7, July 2018. Issue 7 (16th July 2018) - Chang, Irene J.; Sun, Angela; Bouchard, Maryse L.; Kamps, Shawn E.; Hale, Susan; Done, Stephen; Goldberg, Michael J.; Glass, Ian A.
Abstract : The cover image, by Irene J. Chang et al., is based on the Clinical Report Novel Phenotype of Achondroplasia due to Biallelic FGFR3 Pathogenic Variants, DOI:10.1002/ajmg.a.40365 .